Sicker and Poorer - Na Yin (SAGE Publishing, 2015)
Purpose: Disabled individuals younger than 65 years are entitled to Medicare coverage through the Social Security Disability Insurance (DI) program, but only if they have completed a 2-year waiting period. This is the first study that uses longitudinal panel data, the Health and Retirement Study, and examines whether and to what extent the health and economic status are affected among disability beneficiaries who are uninsured during the Medicare waiting period. Methods: In a quasiexperiment research design, using a difference-in-difference (diff-in-diff) estimator, we compare changes in health and economic outcomes pre-/postentering the DI program for disability beneficiaries with alternative public health insurance and those without. Results: The adjusted diff-in-diff estimates suggest that disability beneficiaries who are uninsured during the waiting period, compared to those who are insured, are 13.6 percentage point more likely to report poor health, 6.3 percentage point less likely to be in excellent health, declare more difficulties in activities of daily living, and 30% higher medical expenditures from out of pocket. Conclusions: The findings highlight punitive health and economic effects of the Medicare waiting period for uninsured disability beneficiaries. We also discuss the implications of the findings for the Affordable Care Act reform.